Sorting objects based on weight using the Internet of Things (IoT) - Muhammad Habibi Alfajri, Muhammad; Sukardi (Journal of Industrial Automation and Electrical Engineering, 2024)
This research aims to design and implement a goods sorter based on weight using Arduino Nano, equipped with a web-based monitoring system. The system uses a load cell sensor to detect the weight of items and classify them into three different categories. The Internet of Things (IoT) concept is applied to enable real-time monitoring through Google Sheets, where the sorting data is automatically sent and stored on the web. The test results show that this tool successfully improves efficiency and accuracy in the process of sorting goods in the industry. Additionally, this tool can reduce costs typically incurred for procuring checkweigher devices and ensure compliance with quality standards regulated by consumer protection laws. Based on the analysis of the test data, this system can function well according to the specified requirements, with several recommendations for improving accuracy and further developing monitoring features